Kohesivitas dan Kecerdasan Emosional Perawat terhadap Kinerja Perawat Pelaksana - Yanty Gurning; Bustami Syam; Setiawan Setiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to analyze the effect of nurse cohesiveness and emotional intelligence on the performance of nurses at Bina Kasih General Hospital Medan. The research method used is an analytical survey with a cross-sectional approach. The results showed that the nurse's cohesiveness and emotional intelligence obtained a p-value of 0.001 < = 0.05. The most dominant variable affecting the performance of the implementing nurse is the emotional intelligence variable with a regression coefficient of OR 89.514. In conclusion, nurses' cohesiveness and emotional intelligence have a positive and significant effect on the performance of implementing nurses at Bina Kasih General Hospital Medan. Keywords: Emotional Intelligence, Nurse Performance, Cohesiveness